Eosinophil extracellular DNA trap cell death mediates lytic release of free secretion-competent eosinophil granules in humans - Ueki, Shigeharu (American Society of Hematology, 2013)
Eosinophils release their granule proteins extracellularly through exocytosis, piecemeal degranulation, or cytolytic degranulation. Findings in diverse human eosinophilic diseases of intact extracellular eosinophil granules, either free or clustered, indicate that eosinophil cytolysis occurs in vivo, but the mechanisms and consequences of lytic eosinophil degranulation are poorly understood. We demonstrate that activated human eosinophils can undergo extracellular DNA trap cell death (ETosis) that cytolytically releases free eosinophil granules. Eosinophil ETosis (EETosis), in response to immobilized immunoglobulins (IgG, IgA), cytokines with platelet activating factor, calcium ionophore, or phorbol myristate acetate, develops within 120 minutes in a reduced NADP (NADPH) oxidase-dependent manner. Initially, nuclear lobular formation is lost and some granules are released by budding off from the cell as plasma membrane–enveloped clusters. Following nuclear chromatolysis, plasma membrane lysis liberates DNA that forms weblike extracellular DNA nets and releases free intact granules. EETosis-released eosinophil granules, still retaining eosinophil cationic granule proteins, can be activated to secrete when stimulated with CC chemokine ligand 11 (eotaxin-1). Our results indicate that an active NADPH oxidase-dependent mechanism of cytolytic, nonapoptotic eosinophil death initiates nuclear chromatolysis that eventuates in the release of intact secretion-competent granules and the formation of extracellular DNA nets.